EXPLORING THE ETHICAL DIMENSIONS OF VIRTUAL PRODUCTION: LESSONS FROM QUEERSKINS: FLY ANGEL SOUL - Dr. Illya SZILAK, (Fonseca, Journal of Communication, 2024)
This paper investigates the potential of virtual reality (VR) technology, known for its efficacy in fostering empathy, to serve as a "moral" agent in filmmaking. We explore whether virtual production can contribute to empathy in cinematic storytelling by analyzing our experimental short film, Queerskins: Fly Angel Soul, crafted using three virtual cameras in a responsive virtual mis-en-scene. We also review important neuropsychological and philosophical considerations for promoting empathy in film and virtual reality to provide context.